The Effect of Music and White Noise on Electroencephalographic (EEG) Functional Connectivity in Neonates in the Neonatal Intensive Care Unit. (January 2021) - Akiyama, Akiyoshi; Tsai, Jeng-Dau; W. Y. Tam, Emily; Kamino, Daphne; Hahn, Cecil; Go, Cristina Y.; Chau, Vann; Whyte, Hilary; Wilson, Diane; McNair, Carol; Papaioannou, Vicky; Hugh, Sarah C.; et al.
The purpose of this study is to investigate whether listening to music and white noise affects functional connectivity on scalp electroencephalography (EEG) in neonates in the neonatal intensive care unit. Nine neonates of ≥34 weeks' gestational age, who were already undergoing clinical continuous EEG monitoring in the neonatal intensive care unit, listened to lullaby-like music and white noise for 1 hour each separated by a 2-hour interval of no intervention. EEG segments during periods of music, white noise, and no intervention were band-pass filtered as delta (0.5-4 Hz), theta (4-8 Hz), lower alpha (8-10 Hz), upper alpha (10-13 Hz), beta (13-30 Hz), and gamma (30-45 Hz). Synchronization likelihood was used as a measure of connectivity between any 2 electrodes. In theta, lower alpha, and upper alpha frequency bands, the synchronization likelihood values yielded statistical significance with sound (music, white noise and no intervention) and with edge (between any 2 electrodes) factors. In theta, lower alpha, and upper alpha frequency bands, statistical significance was obtained between music and white noise ( t = 3.12, 3.32, and 3.68, respectively; P < .017), and between white noise and no intervention ( t = 4.51, 3.09, and 2.95, respectively, P < .017). However, there was no difference between music and no intervention. Although limited by a small sample size and the 1-time only auditory intervention, these preliminary results demonstrate the feasibility of EEG connectivity analyses even at bedside in neonates on continuous EEG monitoring in the neonatal intensive care unit. They also point to the possibility of detecting significant changes in functional connectivity related to the theta and alpha bands using auditory interventions.